2019
DOI: 10.1101/716373
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AtDAT1 is a key enzyme of D-amino acid stimulated ethylene production inArabidopsis thaliana

Abstract: Keywords: D-amino acids in plants, D-amino acid-stimulated ethylene production, D-amino acid 9 specific transaminase, D-methionine, 1-aminocyclopropane-1-carboxylic acid, ethylene, amino acid 10 malonylation 11 Manuscript type: Original research 12Abstract 15 D-enantiomers of proteinogenic amino acids (D-AAs) are found ubiquitously, but the knowledge 16 about their metabolism and functions in plants is scarce. A long forgotten phenomenon in this regard 17 is the D-AA-stimulated ethylene production in plants. A… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…This led to the hypothesis that the formation of d -Ala and d -Glu is driven by a d -AA specific transaminase [ 10 , 15 ]. Recently, we confirmed this assumption by the characterization of a previously identified transaminase [ 40 ], which contributes to the metabolization of d -AAs in Arabidopsis [ 41 ]. We could show in this study that loss-of-function mutants of this gene, AtDAT1 , almost completely lose the ability to move the amino group of any given d -AA to either pyruvate or 2-oxoglutarate (2-OG), leading to d -Ala and d -Glu, respectively ( Table 1 ).…”
Section: D-aa Metabolism In Plants: Many Ways To Handlesupporting
confidence: 54%
See 3 more Smart Citations
“…This led to the hypothesis that the formation of d -Ala and d -Glu is driven by a d -AA specific transaminase [ 10 , 15 ]. Recently, we confirmed this assumption by the characterization of a previously identified transaminase [ 40 ], which contributes to the metabolization of d -AAs in Arabidopsis [ 41 ]. We could show in this study that loss-of-function mutants of this gene, AtDAT1 , almost completely lose the ability to move the amino group of any given d -AA to either pyruvate or 2-oxoglutarate (2-OG), leading to d -Ala and d -Glu, respectively ( Table 1 ).…”
Section: D-aa Metabolism In Plants: Many Ways To Handlesupporting
confidence: 54%
“…Further analyses revealed that AtDAT1 is responsible for the decrease of d -Met content by transamination in Arabidopsis plants. The loss of this gene leads to an increased malonylation of d -Met and a reciprocal decrease of malonyl-ACC, the major product of the inactivation of the precursor of ethylene, ACC (1-aminocyclopropane-1-carboxylic acid), as shown in Figure 2 [ 41 ]. In this case, a d -AA ( d -Met) modulates the production of a hormone, and when the activity of the central processing enzyme is lost, the high level of d -Met outcompetes ACC to be malonylated by the N-malonyl-transferase (NMT).…”
Section: Physiological Functions Of D -Aas In Pmentioning
confidence: 99%
See 2 more Smart Citations
“…We believe that multiple specialised enzymes exist to process D-amino acids and ACC. This theory is supported by a recent observation in Arabidopsis, in which D-amino acid transaminase 1 (DAT1) was shown to have a specialised role in D-amino acid metabolism (Suarez et al, 2019). DAT1 is able to transaminate D-methionine into D-alanine, D-glutamic acid and L-methionine.…”
Section: Regulation Of Ethylene Biosynthesis By D-amino Acidsmentioning
confidence: 68%